School Leadership in the Wake of RTE Act 2009: Mapping Changes and Challenges - Diwan, Rashmi (JOURNAL OF INDIAN EDUCATION, 2011)
With changes on two fronts: the social matrix and developments in the education sector, the present era demands a major transformation in the role of School Leaders.The societal awareness levels, change in inter-personal relationships, influx of crime and anti social activities, rise and fall of financial support, demand for removal of social injustice in education and otherwise, students unrest, violence, sex abuse and drug abuse – all such factors lay impact on the ways schools ought to be managed. Within the education domain, the recent act, The Right of Children to Free and Compulsory Education Act, 2009 legitimising the right of each child to have access to good quality education; new education policies and Programme of Action; curriculum changes, global to local; multi language and multi cultural student population; accountability demands and new generation of teachers; teacher power through associations and unions; need for developing linkages with parallel structures, community, NGOs and civil society call for greater transition on the role of School Principals, especially when they have been following conventional management practices and classroom transaction but with a slight change in the curriculum (National Curriculum Framework, 2005). Managing this transition calls for the need to adapt decentralised approach in education system. The paper asserts that School Leaders are of crucial importance for continued improvement of schools provided onus of taking decisions for schools should lie with them. Empowering our School Leaders who can take school-based decisions (may not include financial autonomy) necessitates vital decisions at the policy level. In this context, the paper will discuss about what policy decisions needs to be taken up in a hierarchical and bureaucratic model and in what areas capacity building exercises will help in sustaining leadership to meet the demands emerging from social and educational scenario.